273 CORONARY ARTERIES ANEURYSMS: CASE-BASED DISCUSSION. (15th December 2022) - Di Caccamo, Leandro; Vadalá, Giuseppe; Alaimo, Chiara; Di Fazio, Luca; Ferraiuoli, Giovanni; Buccheri, Giancarlo; Sucato, Vincenzo; Corrado, Egle; Novo, Giuseppina; Galassi, Alfredo Ruggero
Abstract: Coronary artery aneurysm (CAA) is an abnormal dilatation of a coronary artery segment; when its diameter is bigger than 20 mm or it is more than four times bigger as compared to the normal vessel size, the coronary artery aneurysm is defined as Giant. However, there are multiple definition of Giant CAA and miss a standardized classification. The reported prevalence of coronary aneurysms in the population underwent coronary angiography, ranges from 0.3% to 5% and often CAA are found in patient with aneurysms in other sites as ascending or abdominal aorta. In half of the cases an atherosclerotic etiology could be recognized; often CAA is found in the context of acute coronary syndrome. Seldom CAA is found at the autopsy of patient died for sudden cardiac death. Up today very few data exist about CAA management and their prognostic relevance; moreover, CAA treatment is not still clearly codified but rather case-based. Indeed, up today there are not published dedicated studies on which is the best medical therapy in example with antiplatelets or anticoagulant agents rather than an interventional approach, by endovascular or surgical technique. In this review, through two clinical cases, it will be described the current evidence about diagnostic tools and treatment options of CAAs.